2001
DOI: 10.1152/ajpregu.2001.281.5.r1746
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of baseline breathing and of hypercapnic and hypoxic ventilatory responses in newborn mice

Abstract: Breathing during the first postnatal hours has not been examined in mice, the preferred mammalian species for genetic studies. We used whole body plethysmography to measure ventilation (VE), breath duration (T(TOT)), and tidal volume (VT) in mice delivered vaginally (VD) or by cesarean section (CS). In experiment 1, 101 VD and 100 CS pups aged 1, 6, 12, 24, or 48 h were exposed to 8% CO2 or 10% O2 for 90 s. In experiment 2, 31 VD pups aged 1, 12, or 24 h were exposed to 10% O2 for 5 min. Baseline breathing mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 34 publications
(60 reference statements)
3
24
0
1
Order By: Relevance
“…There are precedents for life-sustaining breathing in the absence of CO 2 chemical drive in some situations. In rodents, some (Serra et al, 2001;Stunden et al, 2001) but not all (Wickström et al, 2002) investigators reported a blunted hypercapnic response in 1-week-old rats, but a similar transient drop in CO 2 responsiveness has not been found in mice (Renolleau et al, 2001; this paper). In humans, pronounced hypocapnia induces apnea in sleep, but not in wakefulness during which a still enigmatic "wakefulness drive" is supposed to replace that afforded by CO 2 (Dempsey, 2005;Duffin, 2010).…”
Section: Discussionmentioning
confidence: 45%
“…There are precedents for life-sustaining breathing in the absence of CO 2 chemical drive in some situations. In rodents, some (Serra et al, 2001;Stunden et al, 2001) but not all (Wickström et al, 2002) investigators reported a blunted hypercapnic response in 1-week-old rats, but a similar transient drop in CO 2 responsiveness has not been found in mice (Renolleau et al, 2001; this paper). In humans, pronounced hypocapnia induces apnea in sleep, but not in wakefulness during which a still enigmatic "wakefulness drive" is supposed to replace that afforded by CO 2 (Dempsey, 2005;Duffin, 2010).…”
Section: Discussionmentioning
confidence: 45%
“…Structural brain maturity in mice aged 4, 7, and 10 days roughly corresponds to that in human infants of 26, 36, and 40 weeks' gestational age, respectively (38). The ventilatory response to hypoxia is virtually nonexistent during the first 6 -12 postnatal hours in mice (70) and during the first few days in humans, whereas the ventilatory response to hypercapnia is present at birth in mice (70) and humans. The ventilatory response to hypoxia is biphasic, with an initial increase in ventilation followed by a decrease, which may fall below the prehypoxic level during hypoxia (hypoxic ventilatory decline) or on return to normoxia [post-hypoxic ventilatory decline (20,70,72)].…”
Section: Similarities In Breathing Between Newborn Mice and Human Infmentioning
confidence: 79%
“…The ventilatory response to hypoxia is virtually nonexistent during the first 6 -12 postnatal hours in mice (70) and during the first few days in humans, whereas the ventilatory response to hypercapnia is present at birth in mice (70) and humans. The ventilatory response to hypoxia is biphasic, with an initial increase in ventilation followed by a decrease, which may fall below the prehypoxic level during hypoxia (hypoxic ventilatory decline) or on return to normoxia [post-hypoxic ventilatory decline (20,70,72)]. The magnitude of the hypoxic or post-hypoxic decline closely depends on the strength of the hypoxic stimulus, ambient temperature, and mouse strain, leading to some variability in previously reported data (6).…”
Section: Similarities In Breathing Between Newborn Mice and Human Infmentioning
confidence: 96%
“…• C, this temperature is considered to be close to thermoneutrality in newborn rodents [15,16]), during 90 s (s) and over the CS− odor, associated to cold (26 • C), also for 90 s. Thermographic studies in newborn rats indicate that 26…”
Section: Methodsmentioning
confidence: 99%